Soils, sinks, and smallholder farmers: Examining the benefits of biochar energy transitions in Kenya. (May 2021) - Mahmoud, Yahia; Njenga, Mary; Sundberg, Cecilia; Roing de Nowina, Kristina
Abstract: Besides reducing fuel demands and indoor air pollution, pyrolytic cooking stoves produce a by-product (biochar) that can improve soil fertility and serve as a sink for carbon sequestration. Most smallholder farmers in Africa depend on wood for fuel, suffer from exposure to smoke and soils in their cultivated farms are deteriorating. Biochar (bio-charcoal) production has potentials to reduce energy requirement, diminish exposure to smoke, improve soil health and ease household activities traditionally associated with female labour. However, introducing new technologies and behaviours that tackle existing problems without creating new ones is a complex endeavour. Transitions need to be anticipatory, comprehensive and inclusive. Having this in mind, a trans-disciplinary study was conducted from 2013 to 2019 with 150 households in three agro-ecological zones of Kenya. The socio-economic conditions, the uses of fuels and stoves, the crops grown and fertilizers used, as well as the labour division within households were documented. Selected households were given pyrolitic cooking stoves and trained in applying biochar to the soil. After two years of using the cooking stoves and applying biochar, studies were conducted to assess the feasibility and preliminary impacts based on the households own perceptions and experiences. The results showed that the strategy represented a viable option to deal with fuel use efficiency, exposure to indoor smoke and soil degradation, as well as easing the burden on female labour.